(untitled) (Hoboken, NJ, 2004)
Addresses measurements in new fields such as cellular and molecular biology. Equips readers with the necessary background in electric circuits. Statistical coverage shows how to determine trial sizes.
Keywords: Biological apparatus and supplies,Biotechnology.,Công nghệ sinh học